2019
DOI: 10.1093/rheumatology/kez119
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity burden in axial spondyloarthritis: a cluster analysis

Abstract: Objectives To examine how comorbidities cluster in axial spondyloarthritis (axSpA) and whether these clusters are associated with quality of life, global health and other outcome measures. Methods We conducted a cross-sectional study of consecutive patients meeting ASAS criteria for axSpA in Liverpool, UK. Outcome measures included quality of life (EQ5D), global health and disease activity (BASDAI). We used hierarchical clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 27 publications
(35 reference statements)
3
34
0
4
Order By: Relevance
“…47 studies were of AS (including 32 using modi ed New York criteria) and 17 of axSpA (including 11 using the ASAS criteria). Delay ranged from 2.8 years in a small Albanian study (of 54 cases over 6 years), to 11.1 years in a single UK centre [13,14]. The mean delay to diagnosis was 6.7 years overall (95% con dence interval 6.2 to 7.2, I 2 =99%).…”
Section: Diagnostic Delay In Axspamentioning
confidence: 94%
“…47 studies were of AS (including 32 using modi ed New York criteria) and 17 of axSpA (including 11 using the ASAS criteria). Delay ranged from 2.8 years in a small Albanian study (of 54 cases over 6 years), to 11.1 years in a single UK centre [13,14]. The mean delay to diagnosis was 6.7 years overall (95% con dence interval 6.2 to 7.2, I 2 =99%).…”
Section: Diagnostic Delay In Axspamentioning
confidence: 94%
“…38 studies were of AS (including 25 using modified New York criteria) and 18 of axSpA (including 11 using the ASAS criteria). Delay ranged from 2.8 years in a small Albanian study (of 54 cases over 6 years), to 11.1 years in a single UK centre [12,13]. The mean delay to diagnosis was 6.8 years overall (95% confidence interval 6.2 to…”
Section: Diagnostic Delay In Axspamentioning
confidence: 95%
“…AS is a subtype of axSpA and presents typical radiographic manifestations. AS can cause physiological damage, disability, and neurological deafness [3,4], leading to reduced quality of life (QOL) and placing a substantial financial burden on patients, their families and society [5][6][7]. An American study on the direct and indirect economic burden of patients with AS showed that the average direct medical costs were $2674 during the first year, while the indirect costs were $4945 [8].…”
Section: Introductionmentioning
confidence: 99%